Current estimates of the economic burden of blindness and visual impairment in India: A cost of illness study - Sunny Mannava; Rishi Raj Borah; B R Shamanna (Indian Journal of Ophthalmology, 2022)
Purpose: Currently, there are an estimated 4.95 million blind persons and 70 million vision impaired persons in India, out of which 0.24 million are blind children. Early detection and treatment of the leading causes of blindness such as cataract are important in reducing the prevalence of blindness and vision impairment. There are significant developments in the field of blindness prevention, management, and control since the “Vision 2020: The right to sight” initiative. Very few studies have analyzed the cost of blindness at the population level. This study was undertaken to update the information on the economic burden of blindness and visual impairment in India based on the prevalence of blindness in India. We used secondary and publicly available data and a few assumptions for our estimations. Methods: We used gross national income (GNI), disability weights, and loss of productivity metrics to calculate the economic burden of blindness and vision impairment based on the “cost of illness” methodology. Results: The estimated net loss of GNI due to blindness in India is INR 845 billion (Int$ 38.4 billion), with a per capita loss of GNI per blind person of INR 170,624 (Int$ 7,756). The cumulative loss of GNI due to avoidable blindness in India is INR 11,778.6 billion (Int$ 535 billion). The cumulative loss of GNI due to blindness increased almost three times in the past two decades. The potential loss of productivity due to vision impairment is INR 646 billion (Int$ 29.4 billion). Conclusion: These estimates provide adequate information for budgetary allocation and will help advocate the need for accelerated adoption of all four strategies of integrated people-centered eye care (IPCEC). Early detection and treatment of blindness, especially among children, is very important in reducing the economic burden; thus, there is a need for integrating primary eye care horizontally with all levels of primary healthcare.